The effect of nitrogen supply on specific yield and fruit quality of apple (Malus domestica Borkh.) - Racskó, J.; Nagy, J.; Soltész, Z.; Soltész, M.; Nagy, P. T.; Nyéki, J.; Holb, I. J. (International Journal of Horticultural Science, 2005)
The aim of the present study was to determine the effect of nitrogen supply on yield and fruit quality of apple cultivars and to explore the relationships between canopy density and the different fruit quality parameters.The experiments were carried out at Kálmánháza, in Eastern Hungary in a private orchard in 2003-2004. The response of four apple cultivars ('Elstar', 'Gala Prince', 'Granny Smith', 'Idared') to different nitrogen dosages was studied. The assessed and calculated indices were: yield, fruit diameter, fruit height, shape index, fruit mass, firmness, dry matter content and colouration. The results indicated that nitrogen fertilization has a significant effect on the yield and fruit quality of apple cultivars. The calculated specific yield values were reduced by the application of nitrogen via the increase in the volume of the canopy. An opposit trend was observed for fruit diameter, fruit height and fruit weight, which increased with increasing nitrogen supply. The reduced shape index caused flattening of fruits.However, the improvement of fruit quality via increasing nitrogen dosage is only virtual, since these dosages increase the fruit size, but firmness, dry matter content and colouration are diminished, which decreases the value of the fruits on the market.The authors also studied the relationships between canopy density responsible for assimilation and light supply of the fruits and the different fruit quality parameters. The closest linear inversely proportional relationship was found in the case of colouration. There was a negative linear relationship between canopy density and firmness or dry matter content. The relationship between canopy density and fruit mass could be described by a quadratic polinomial function.